The researcher’s “self” in the auto/biographical approach. A methodological perspective - Pryszmont-Ciesielska, Martyna (Auto/biograficzne aspekty praktyk poznawczych, 2016)
The text concerns the possibilities to employ the auto/biographical approach in research on education. The researcher’s personal biography may not only define the perspective for scholarly cognition but also become the research object itself. The author ponders about how to mark and place the biography of the cognitive subject in the research process. The presented text is an attempt to answer this question and find a methodological justification for such research practices. In order to achieve that the author describes selected approaches: the biographical and ethnographic approach as well as action research, which allow incorporating the researcher’s “self” in their research. The author then proposes some methods for researchers to write about themselves which give them the ability to present their own autobiographical account.